Full-time Workers Want to Work Fewer Hours, Part-time Workers Want to Work Longer Hours - Elke Holst (Weekly Report, 2009)
Since the reunification of Germany, average working times for men and women have followed different trends. There are various reasons for the difference. More and more women are gainfully employed; they engage in part-time and marginal employment, both of which are on the rise. The importance of full-time employment has declined. This accounts for most of the reduction in their average workweek, which decreased by 2.3 hours to 31.9 hours between 1993 and 2007. The full-time employment of men also declined, in both relative and absolute terms-unlike their average workweek, which, according to data provided by the German Socio-Economic Panel (SOEP), totaled 43.3 hours per week in 2007. This is 0.8 hours more than in 1993. Overall, the working time of male and female wage and salary earners in West Germany and of such earners in East Germany have converged, though not the number of working hours preferred by women in the two regions. These numbers remain considerably higher in East Germany than in West Germany. The differences are most pronounced among women who work part-time. In East Germany, the women who this applies to often find that this form of employment provides too low a level of work. Long workweeks exceeding 40 hours are not very popular in either part of Germany-not even among men, at least half of whom work that long, though only 17 percent of them do so by preference.
Keywords: J16; J21; J22; 330; Working time; Working time preferences; Gender gap; East / West Germany